The history augmented Solow model - Carl-Johan Dalgaard; Holger Strulik (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2010)
Unified growth theory predicts that the timing of the fertility transition is a key determinant of contemporary comparative development, as it marks the onset of the take-off to sustained growth. Neoclassical growth theory presupposes a take-off, and explains comparative development by variations in (subsequent) investment rates. The present analysis integrates these two perspectives empirically, and shows that they together constitute a powerful predictive tool vis-a-vis contemporary income differences.
Keywords: O11; O57; 330; Comparative Development; Unified Growth Theory; Neoclassical Growth Theory; Entwicklung; Vergleich; Wachstumstheorie; Demographischer Übergang; Investition; Theorie